Toward improved corrections for radiation‐induced biases in radiosonde temperature observations. Issue 10 (28th May 2013) - Sun, Bomin; Reale, Anthony; Schroeder, Steven; Seidel, Dian J.; Ballish, Bradley
Abstract: [1] Radiation‐induced biases in global operational radiosonde temperature data from May 2008 to August 2011 are examined by using spatially and temporally collocated Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) data as estimates of the truth. The data on average from most radiosonde types show a nighttime cold bias and a daytime warm bias relative to COSMIC. Most daytime biases increase with altitude and solar elevation angle (SEA). The global average biases in the 15–70 hPa layer are −0.05 ± 1.89 K standard deviation (~52, 000 profiles) at night and 0.39 ± 1.80 K standard deviation (~64, 500 profiles) in daytime (SEA > 7.5°). Daytime warm biases associated with clouds are smaller than those under clear conditions. Newer sondes (post‐2000) have smaller biases and appear to be less sensitive to effects of clouds. Biases at night show greater seasonal and zonal variations than those for daytime. In general, warm night biases are associated with warm climate regimes and less warm or cold night biases with cold climate regimes. Bias characteristics for 13 major radiosonde types are provided, as a basis for updating radiosonde corrections used in numerical weather predictions, for validating satellite retrievals, and for adjusting archived radiosonde data to create consistent climate records. Key Points: The analysis aims to facilitate improvements in radiosonde bias corrections